Analisis Kebijakan Ekonomi Umar Bin Khattab Perspektif Bisnis Syariah - Dwi Hidayatul Firdaus (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2013)
As one comprehensive life system, Islam trusted by its as teaching which in general instruct human being to obtain; get two bliss dimension, that is eternity and world. Beside load order about problem of theology, aqidah, religious service, Islam also give fringes about problem of economics, either through and also implisit of explisit As khalifah both, successful Umar Bin Khattab in arranging political economy and governance. Might not be wrong if said that Umar Khattab bin have shown to world that applying of holy syariat is not at all hinder creative energy and innovate the highest leader a state in realizing prosperous and peaceful state. Beside give defiition , fringes and patron to be each; every policy shariah do not become source damn, also give very strong motivation and motivation to leader to strive to realize what most mashlahat its peoples.